MENJEMBATANI WAHYU DAN INTERVENSI: SEBUAH KERANGKA BIMBINGAN KONSELING ISLAM UNTUK PENCEGAHAN PERUNDUNGAN BERDASARKAN PRINSIP-PRINSIP AL-QURAN - Nofita Rahmawati, Roro Kurnia (Institut Dirosat Islamiyah Al-Amien Prenduan, 2026)
Bullying in Islamic schools requires a counseling approach aligned with spiritual values. This study developed and tested an integrative Islamic counseling model for bullying prevention based on Qur'anic principles. Using the Research and Development method, the research produced the Qur'anic Relational Restoration (QRR) Model. This operational framework consists of four phases: Ta‘arruf (Holistic Introduction), Tafh?m (Empathetic Understanding), Ta‘?wun (Collaborative Action), and Taqy?m (Continuous Evaluation). It translates principles like ?if? al-Kar?mah (preserving dignity) into specific techniques such as Guided Qur'anic Reflection (GQR). Validation by experts yielded a high Content Validity Index (CVI) of 0.92. A limited trial with counselors confirmed its practicality and effectiveness in building client insight and therapeutic rapport. The study concludes that the QRR Model is a valid, practical, and contextually authentic tool for Islamic schools to address bullying, effectively bridging spiritual principles with psychological intervention.